2013
DOI: 10.1371/journal.pone.0078825
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Damage of Loligo vulgaris and Illex coindetii statocysts after Low Frequency Sound Exposure

Abstract: There is a considerable lack of information concerning marine invertebrate sensitivity to sound exposure. However, recent findings on cuttlefish and octopi showed that exposure to artificial noise had a direct consequence on the functionality and physiology of the statocysts, sensory organs, which are responsible for their equilibrium and movements in the water column. Owing to a lack of available data on deep diving cephalopod species, we conducted a noise exposure comparative experiment on one Mediterranean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…Our previous works on cephalopods presented the first morphological and ultrastructural evidence of a massive acoustic trauma induced on individuals belonging to four cephalopod species ( S. officinalis, O. vulgaris, L. vulgaris and I. coindetii ) by low frequency sound Controlled Exposure Experiments (CEE), in laboratory conditions353637. The consequences of such CEE were permanent and substantial alterations of the sensory hair cells of the statocysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works on cephalopods presented the first morphological and ultrastructural evidence of a massive acoustic trauma induced on individuals belonging to four cephalopod species ( S. officinalis, O. vulgaris, L. vulgaris and I. coindetii ) by low frequency sound Controlled Exposure Experiments (CEE), in laboratory conditions353637. The consequences of such CEE were permanent and substantial alterations of the sensory hair cells of the statocysts.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies on invertebrate sensitivity to noise and possible negative effects after sound exposure have been recently published25262728293031323334. A detailed literature review on these effects can be found in recent publications353637.…”
mentioning
confidence: 99%
“…Invertebrates, such as cephalopods have been documented to experience significant trauma after exposure to intense low-frequency signals (Solé et al 2013), as well as physiological and behavioral changes during exposure to seismic airguns (McCauley et al 2000, Fewtrell & McCauley 2012. Aguilar de Soto et al (2013) reported malformations and delayed development of scallop larvae due to controlled exposure to seismic pulse playbacks.…”
Section: Discussionmentioning
confidence: 99%
“…The statocyst is analogous to the fish otolith system (Fay, 1974) and, to some extent, may share functions of the inner ear hair cells of higher vertebrates (Yost, 1994). Because squid are now considered to respond to some acoustic components, there is concern that increases in ocean noise may damage statocyst hair cells and impact their hearing (Packard et al, 1990;Budelmann et al, 1992;Kaifu et al, 2008;Hu et al, 2009;André et al, 2011;Mooney et al, 2012;Solé et al, 2013). Additionally, squid have been a model species in physiology and neuroscience since the classic experiments by Hodgkin and Huxley on the nature of the action potential Huxley, 1945, 1952), and their use is growing in other areas such as the study of camouflage and animal-bacterial symbioses (Hanlon, 2007;Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The sensory epithelia are robust, surviving for hours after dissection without complex culture media (Budelmann and Williamson, 1994). Despite thorough investigation using classical dissection and scanning electron microscopy studies (Budelmann et al, 1973;Dilly, 1976;Stephens and Young, 1982;Solé et al, 2013), the statocyst and other systems of cephalopods are just beginning to be explored with advanced imaging and electrophysiological techniques. Developing molecular techniques is both appropriate and timely given the advances in techniques and applications for squid as a model system.…”
Section: Introductionmentioning
confidence: 99%